2013
DOI: 10.1558/cj.v17i3.395-429
|View full text |Cite
|
Sign up to set email alerts
|

Using Instructional Video to Teach Culture to Beginning Foreign Language Students

Abstract: This investigation examines whether foreign language (FL) students learn cultural information embedded in videos. Fifty beginning French students participated. They viewed eight targeted videos as part of their multimedia-based curriculum. A pretest and a posttest assessed long-term gains in overall cultural knowledge and in the learning of little "c" culture (practices) and big "C" culture (products). Eight postvideo tests measured short-term retention of culture in each of the eight videos. Oral dialogues te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Beyond the effects illustrated by Herron and colleagues (, , ), there are many advantages to authentic video in L2 teaching. The most basic are availability (via the Internet, for example) and relative low cost.…”
Section: Review Of Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond the effects illustrated by Herron and colleagues (, , ), there are many advantages to authentic video in L2 teaching. The most basic are availability (via the Internet, for example) and relative low cost.…”
Section: Review Of Researchmentioning
confidence: 99%
“…Researchers have investigated the effects of integrating video in L2 French classrooms at the beginning (Herron, Corrie, Cole, & Dubreil, 1999;Herron, Dubreil, Cole, & Corrie, 2000) and intermediate levels (Herron, Corrie, Dubreil, & Cole, 2002). In both cases, they found signifi cant gains in cultural knowledge over the course of a semester in which 10 (Herron, Corrie, Cole, et al, 1999) or eight (Herron, Dubreil, et al, 2000;Herron, Corrie, Dubreil, et al, 2002) videos had been incorporated into the curriculum. Their results, taken together especially, suggest that fi lm in the L2 classroom is benefi cial for learners in a measurable way.…”
Section: Using Film In An L2 Classroommentioning
confidence: 99%
“…In this research, a quantitative analytical method was chosen to monitor student performances between the three academic periods considered in this research (i.e., 2011, 2012, and 2013). A review of the literature suggests that the most commonly applied method to assess the impacts of technologies on student performance is the one-way analysis of variance (ANOVA; Blanchard et al, 1998;Herron et al, 2000;Mahdjoubi & A-Rahman, 2012;Zhang & Chawla, 2012;Zhang et al, 2006). Other frequently used methods included x 2 and Kruskal -Wallis test (Fagin & Wikle, 2011), and t-test (Taylor et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Instructional videos have recently been applied in different educational fields, such as nursing (Chandler & Hanrahan, 2000), medical science (Zhang & Chawla, 2012), architecture (Mahdjoubi & A-Rahman, 2012), engineering (Zhang et al, 2006), product marketing (Huarng, Yu, & Huang, 2010), cultural studies (Herron, Dubreil, Cole, & Corrie, 2000), motivation building studies (Kalichman, Cherry, & Browne-Sperling, 1999), and dairy health management (Vidya & Manivannan, 2010). Generally, these studies have shown that when used in moderation, a video can improve the learning experiences by providing the learner with a detailed visual description of the concept being taught.…”
Section: Video Technologymentioning
confidence: 99%
See 1 more Smart Citation